PERSISTENSI PENGGUNAAN ANTIHIPERTENSI SEBAGAI PREDIKTOR KEJADIAN DAN BIAYA RAWAT INAP PADA PASIEN HIPERTENSI PESERTA ASURANSI PT ASKES (PERSERO) DI RSUD PANEMBAHAN SENOPATI BANTUL - , NURMAINAH, SSI.,APT.,MM; , Prof. Dr. Achmad Fudholi, D.E.A., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Persistence of the use of antihypertensive drugs in hypertensive patients greatly needed. Considering the primary outcome of treatment for hypertension is to reduce or prevent the occurence of cardiovascular events such as myocardial infarction, stroke that led to the risk of death. This study aims to determine whether the use of antihypertensive persistence is a predictor for the occurrence of cardiovascular events and costs. This study was designed with retrospective cohort study. It was conducted by collecting the claimed prescribing database of the hypertension outpatients covered by health insurance (Askes) who used antihypertension in Panembahan Senopati Public Hospitals Bantul. This cohort study involving 304 patients using antihypertensive medications first (index date of therapy 1 July 2007-31 December 2008). Data analysis used in the study included chi-square analysis, Kaplan-Meierâs survival analysis, and coxâs proportion hazard test, and logistic regression. After observation for 3-4.5 years found that the dominant factor effect on the incidence of hospitalization in hypertensive patients covered by insurance of PT Askes (Persero) is a gender factor. Men are more at risk for hospitalization than women because men are not persistent in the use of antihypertensive drugs than women (RR= 1.73